2017
DOI: 10.3168/jds.2016-12085
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between body condition score change, prior mid-lactation phenotypic residual feed intake, and hyperketonemia onset in transition dairy cows

Abstract: Extensive efforts have been made to identify more feed-efficient dairy cows, yet it is unclear how selection for feed efficiency will influence metabolic health. The objectives of this research were to determine the relationships between residual feed intake (RFI), a measure of feed efficiency, body condition score (BCS) change, and hyperketonemia (HYK) incidence. Blood and milk samples were collected twice weekly from cows 5 to 18 d postcalving for a total of 4 samples. Hyperketonemia was diagnosed at a blood… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
55
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(66 citation statements)
references
References 35 publications
8
55
0
3
Order By: Relevance
“…The peripartum BCS and a series of changes, including the BCS at calving and the rate and degree of BCS reduction after calving, may indicate the increase of non-esterified fatty acids, possibility of postpartum diseases and differences in production performance. Studies have shown that the BCS of multiparous cows can be regarded as a prediction tool due to the strong association between the BCS and metabolic diseases, including hepatic lipidosis, ketosis, and abomasum displacement [11][12][13]. The main reason for this strong association is that weight loss over 50 kg due to improper prepartum feeding significantly inhibits DMI and milk production; meanwhile, high milk production and the consequent synthesis of milk fat result in a high degree of fat mobilization, causing cows to go through NEB [14].…”
Section: Introductionmentioning
confidence: 99%
“…The peripartum BCS and a series of changes, including the BCS at calving and the rate and degree of BCS reduction after calving, may indicate the increase of non-esterified fatty acids, possibility of postpartum diseases and differences in production performance. Studies have shown that the BCS of multiparous cows can be regarded as a prediction tool due to the strong association between the BCS and metabolic diseases, including hepatic lipidosis, ketosis, and abomasum displacement [11][12][13]. The main reason for this strong association is that weight loss over 50 kg due to improper prepartum feeding significantly inhibits DMI and milk production; meanwhile, high milk production and the consequent synthesis of milk fat result in a high degree of fat mobilization, causing cows to go through NEB [14].…”
Section: Introductionmentioning
confidence: 99%
“…En el 2001 en un hato en Florida, se tomaron muestras de sangre y leche para determinar concentraciones de βHB de 300 vacas suplementadas con monensina ante parto, se definió cetosis subclínica cuando los valores de βHB en sangre fueran ≥1,0 mmol/L y en leche ≥ 200 μmol/L encontrándose una prevalencia global de cetosis subclínica del 20,4% sin diferencias significativas entre las tratadas con monensina y los controles, sin embargo, la prevalencia de la enfermedad a concentraciones ≥1,2 mmol/L y a ≥1,4 mmol/L fue solo del 8% y 4% 58 y la incidencia en los animales no tratados fue del 26,6%, similar a lo reportado por Rathbun et al, (2017), para quienes la incidencia en 570 vacas en Wisconsin fue del 19,7% 59 , resultados que difieren a lo encontrado en dos hatos en Nueva York y dos hatos en Wisconsin en el 2010, donde se determinó la concentración de βHB en sangre, entre el 3 al 16 día postparto estableciendo como positivas, vacas con valores ≥ 1,2 mmol/L; de las 1717 vacas incluidas en el estudio, el 43,2% fueron diagnosticadas al menos una vez con cetosis subclínica, con una variación en la incidencia entre hatos del 26 y 56% y un pico de incidencia a los cinco días en leche 35 , mientras que, en un estudio en 118 vacas en un hato comercial en Michigan, dentro de los primeros 5 a 17 días en leche, en el que se evaluó la concentración de βHB en sangre y en leche, se obtuvo una prevalencia del 33,1% y del 39,8% respectivamente 60 . Sin embargo, una prevalencia más baja se reportó en cinco hatos en Colorado en 446 vacas, determinada por las concentraciones de βHB en sangre y en leche, siendo del 12% durante los primeros 14 días posparto 61 .…”
Section: Cetosis Subclínica En Estados Unidosunclassified
“…Increased liver inflammation has been linked to higher occurrence of TD (Bertoni et al, 2008). This may explain the observed association between body condition loss during the dry period and the occurrence of uterine diseases (Chebel et al, 2018) and SCK (Kaufman et al, 2016;Rathbun et al, 2017). Although the etiologies of infectious and metabolic diseases differ, it seems that DMI and body condition loss The relationship between transition period diseases and lameness, feeding time, and body condition during the dry period underpin some of the mechanisms that contribute to disease vulnerability.…”
Section: Introductionmentioning
confidence: 99%